Ecstasy: a synthetic history of MDMA - Clark, Peder (Routledge handbook of intoxicants and intoxication, 2023)
First patented by Merck in the early twentieth century, and reinvented by American chemists in the 1960s and 1970s, MDMA (3,4-methylenedioxymethamphetamine) has been characterised as a good-time party drug with a dark side. Ecstasy, ‘E’, ‘X’ or ‘molly’ is connected in contemporary parlance with EDM mega-raves and the sometimes lethal consequences of over-consumption. This chapter suggests that historians and other critical drugs researchers might look beyond these binaries of hedonism and harm to develop more nuanced perspectives on ecstasy. It does so by providing a ‘synthetic history’ that moves beyond existing work which focuses either on the moral panics periodically associated with ecstasy or the apparently universalising affect that its consumers report. The first half of this chapter concentrates on the birth and reinvention of MDMA in Germany and the US, while the second half considers ecstasy’s arrival in Britain and entwinement with the ‘rave’ scene. By exploring some of the radically different experiences of the drug even within these relatively culturally homogenous contexts, it makes the case that ecstasy is and was a historically contingent intoxicant. Not only is this apparent from a pharmacological perspective (for example, ecstasy pills in the 2010s were consistently and considerably stronger than their 1990s antecedents), but the ‘hyper-specific’ spaces and scenes in which MDMA was consumed, alongside structural factors such as gender, race or class, mean that ecstasy’s characterisation as a universalising intoxicant deserves to be more closely interrogated.